Seating and wheeled mobility : a clinical resource guide - Lange, Michelle L.; Minkel, Jean, 1958- (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Fully revised and updated in its second edition, Seating and Wheeled Mobility: A Clinical Resource Guide presents clinical assessment considerations when working with a person with a disability who may need wheelchair seating for postural support and to protect skin integrity, or a wheelchair base to best meet dependent or independent mobility needs. Richly illustrated throughout, this book has been carefully designed to support occupational and physical therapists, complex rehabilitation technology suppliers, and third-party payers who are interested in wheelchair seating and mobility assessment and applications"-- Provided by publisher.
Keywords: Disability evaluation; Posture; MEDICAL / Allied Health Services / Occupational Therapy